Method for graded extraction of lignin and preparation of lignin nano-microspheres with adjustable particle size

The preparation of lignin nano microspheres of different particle sizes through fractional extraction and solvent replacement methods has solved the problem of low lignin utilization efficiency in the prior art, and achieved efficient extraction and high-value utilization.

CN119529312AActive Publication Date: 2025-02-28QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411867023.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize lignin, resulting in most of it being burned as fuel and failing to achieve efficient utilization.

Method used

By adjusting the reaction conditions, lignin is extracted in stages, and lignin nanomicrospheres of different particle sizes are prepared by solvent replacement method. The specific steps include mixing poplar powder with a solvent, gradually reducing the pH value of the reaction system or raising the temperature, and then replacing the solvent with a low eutectic solvent and water to prepare lignin nano microspheres with adjustable particle size.

Benefits of technology

The extraction efficiency of lignin was significantly improved, and lignin nano microspheres with large specific surface area, high surface atomic proportion and strong surface modification ability were obtained, achieving high-value utilization of lignin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529312A_ABST
    Figure CN119529312A_ABST
Patent Text Reader

Abstract

The invention discloses a method for graded extraction of lignin and preparation of lignin nano-microspheres with adjustable particle size, and belongs to the technical field of lignin nano-material preparation. The poplar powder is used as an extraction raw material, the temperature or pH value of a reaction system is adjusted, the reaction intensity is adjusted, then graded extraction of lignin and regulation and control of a chemical structure are achieved, the extraction efficiency of lignin is remarkably improved, and lignin of different structures is obtained; and the lignin nano-microspheres with large specific surface area, adjustable particle size, high surface atom number ratio and strong surface modifiability are prepared by taking the graded extracted lignin as a raw material, so that an important theoretical basis is laid for separation extraction and high-value utilization of the lignin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lignin nano material preparation, and more specifically relates to a method for fractionally extracting lignin and preparing lignin nano microspheres with adjustable particle size. Background Art

[0002] Wood fiber raw materials are one of the most abundant green raw materials in the world, and their comprehensive utilization has far-reaching significance. Due to the complex composition structure of lignin, it is difficult to be effectively utilized. At present, lignin is mainly used as fuel for combustion and heat release, so most of it cannot be effectively utilized. Therefore, achieving efficient utilization of lignin is particularly important for the utilization of all components of wood fiber raw materials.

[0003] Lignin nanomaterials have excellent properties such as large specific surface area, relatively high number of surface atoms and surface modifiability, and can be used in a variety of fields. Therefore, exploring the relationship between the molecular structure of lignin and the construction of lignin nanoparticles and preparing high-yield, uniform-sized and well-dispersed highly active lignin nanoparticles through green, economical and simple methods is a major challenge to achieve high-value utilization of lignin. Summary of the invention

[0004] The purpose of the present invention is to provide a method for fractionating lignin and preparing lignin nanoparticles with adjustable particle size, so as to solve the problems existing in the above-mentioned prior art, prepare high-yield, uniform-sized and highly active lignin nanoparticles with good dispersibility, and realize the high-value utilization of lignin.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a method for adjusting reaction conditions to extract lignin in a graded manner and prepare lignin nanoparticles of different particle sizes, comprising the following steps:

[0007] Step 1: mixing poplar wood powder and a solvent to react to obtain a solid phase and a liquid phase;

[0008] Step 2: Using the solid phase as the raw material, repeat the reaction in step 1, and gradually reduce the pH value of the reaction system or gradually increase the temperature of the reaction system during the repetition process;

[0009] The liquid phases obtained in step 1 and step 2 are respectively mixed with a hydrochloric acid solution, and washed and freeze-dried in sequence to obtain lignin;

[0010] The low eutectic solvent is used as solvent and water is used as replacement solvent. The obtained lignin is treated by solvent replacement method to obtain lignin nanoparticles with different particle sizes.

[0011] The present invention uses poplar wood powder as an extraction raw material, adjusts the intensity of the reaction by changing the pH value or temperature of the reaction system, thereby realizing the graded extraction of lignin and the regulation of the chemical structure, significantly improving the extraction efficiency of lignin and obtaining lignin with different structures. When the lignin molecular weight is lower, the content of β-O-4 connecting bonds contained in the lignin is lower, and the content of H-type lignin is higher, the lignin raw material is more conducive to forming lignin nanoparticles with uniform particle size and smaller size through an anti-solvent titration method; and lignin nano-microspheres with large specific surface area, high surface atomic number ratio and strong surface modifiability are prepared through the above-mentioned regulation.

[0012] The specific analysis is as follows:

[0013] Adjusting the temperature of graded extraction: Analysis of the 2D-NMR quantitative results of poplar lignin obtained by adjusting the temperature of graded extraction shows that in the poplar raw material lignin, the content of H-type lignin is small, and H-type lignin is preferentially extracted at 120°C, so H-type lignin is not detected in the subsequent extracted lignin. As the temperature increases from 120°C to 140°C, S / G increases, mainly because S-type lignin is easier to remove with the increase in temperature. When the graded extraction temperature continues to increase, S / G decreases, which is mainly due to the fact that more G-type lignin is removed under severe conditions, so with the increase in temperature, S / G first increases and then decreases. The content of β-O-4, β-β and β-5 linkages in lignin continues to increase with the increase in lignin extraction temperature, indicating that the lignin linkages in the solid residue are less depolymerized and the structure is more complete. Lignin rich in these linkages is better extracted, and these linkages are more stable. The contents of β-β and β-5 are very low at 180℃, indicating that the lignin containing these two types of linkages has been extracted in the previous extraction. w ) gradually increased with the increase of extraction temperature and reached the maximum at 180 °C. n ) also increases with the increase of temperature, indicating that with the increase of reaction temperature, G-type lignin with rich connecting bonds is extracted, which increases the molecular weight of lignin.

[0014] Adjusting the pH value of graded extraction: The 2D-NMR quantitative results of poplar lignin obtained by adjusting the pH value of graded extraction show that as the pH value decreases, the S / G of lignin decreases. This is mainly because at pH = 7, S-type lignin is easier to remove, and the remaining G-type lignin is more. As the pH value decreases, G-type lignin will be further removed under severe conditions. The contents of β-O-4, β-β and β-5 increase with the decrease of pH value, indicating that lignin rich in these types of connecting bonds in the solid residue is better extracted and these types of connecting bonds are relatively stable. The weight average molecular weight (Mw) of graded extracted lignin increases first with the decrease of extraction pH value. When pH = 3, the weight average molecular weight is the largest (2797g / mol). As the acidity continues to increase, the molecular weight of the extracted lignin decreases. The change trend of the number average molecular weight (Mn) is the same, indicating that when the acid concentration of the reaction solution is high, lignin undergoes a certain degree of depolymerization, resulting in a decrease in the molecular weight of lignin.

[0015] The present invention gradually reduces the pH value of the reaction system or gradually increases the temperature of the reaction system, thereby increasing the intensity of the reaction. The extraction efficiency of lignin increases first and then decreases as the pH value decreases. The lignin extraction rate reaches a maximum value of 3.57% when the pH value is 5. The pH value continues to decrease, and the lignin extraction rate decreases. As the temperature increases, the extraction efficiency of lignin gradually decreases.

[0016] Preferably, the step of gradually reducing the pH value of the reaction system comprises: using the solid phase as the raw material, repeating step 1, and gradually reducing the pH value of the reaction system to a pH value of 7, 6, 5, 4, 3, 2 or 1, and the reaction temperature is 120-180°C.

[0017] Preferably, the step of gradually increasing the temperature of the reaction system comprises: taking the solid phase as the raw material, repeating step 1, and gradually increasing the temperature of the reaction system to 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, and the pH value of the reaction is 1 to 7.

[0018] Preferably, the reaction time is 0.5 to 1 h.

[0019] Preferably, the solvent is an ethanol aqueous solution, the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1-5; the solid-liquid ratio of the poplar wood powder to the solvent is 1g:5-10mL.

[0020] Preferably, the pH value of the hydrochloric acid solution is 2, and the volume ratio of the liquid phase to the hydrochloric acid solution is 1:5-10.

[0021] Preferably, the freeze-drying temperature is -50°C, and the freeze-drying time is 24 to 72 hours.

[0022] Preferably, the low eutectic solvent is prepared from lactic acid and choline chloride, and the mass ratio of the lactic acid to choline chloride is 5 to 2:1.

[0023] Preferably, the steps of the solvent replacement method include: mixing lignin and a low eutectic solvent to obtain a mixed solution, and dripping water into the mixed solution; the dripping speed of the water is 0.1 to 0.4 mL / s.

[0024] The second technical solution of the present invention is to provide a method for regulating the particle size of lignin nano-microspheres, using poplar wood powder as raw material and ethanol aqueous solution as solvent, extracting lignin in stages by adjusting the pH value of the reaction system or adjusting the temperature of the reaction system, and then using a solvent replacement method to separately treat the obtained lignin to obtain lignin nano-microspheres of different particle sizes.

[0025] Preferably, the lignin nanospheres with gradually increasing particle sizes are obtained by gradually lowering the pH value of the reaction system; or, the lignin nanospheres with gradually increasing particle sizes are obtained by gradually increasing the temperature of the reaction system.

[0026] The present invention discloses the following technical effects:

[0027] 1. The solvent (ethanol / water) used for fractional extraction of lignin in the present invention is low-priced and environmentally friendly. By adjusting the extraction conditions (temperature or pH value) and the intensity of the extraction, not only the extraction efficiency of lignin is improved, but also the structure of lignin is successfully regulated, which lays the foundation for obtaining lignin nanoparticles with large specific surface area, high surface atomic number ratio and strong surface modifiability;

[0028] 2. The present invention uses a low eutectic solvent system of choline chloride / lactic acid to dissolve lignin, and uses a simple solvent replacement method to obtain lignin nanoparticles, which lays an important theoretical foundation for the separation, extraction and high-value utilization of lignin. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the particle size distribution diagram of lignin nanospheres prepared from lignin L-7 in Example 1;

[0030] Figure 2 This is the particle size distribution diagram of lignin nanospheres prepared from lignin L-5 in Example 1;

[0031] Figure 3 This is the particle size distribution diagram of lignin nanospheres prepared from lignin L-120 in Example 2;

[0032] Figure 4 This is a SEM image of lignin nanospheres prepared from lignin L-120 in Example 2;

[0033] Figure 5 This is the particle size distribution diagram of the lignin nanospheres prepared from lignin L-140 in Example 2. DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] The preparation steps of the deep eutectic solvent used in the following examples are as follows: lactic acid and choline chloride are mixed in a mass ratio of 2:1, and heated in a water bath at 60° C. for 2 h to obtain a transparent deep eutectic solvent;

[0040] The particle size of the poplar wood powder used was 50 mesh;

[0041] Other raw materials used are commercially available products unless otherwise specified.

[0042] Example 1

[0043] With poplar wood powder as raw material, first use ethanol aqueous solution without acid as reaction liquid (ethanol: water = 1:1, v / v, pH = 7) at 180 ° C for 1 hour, the solid-liquid ratio is 1:10 (1g poplar wood powder: 10mL reaction liquid), after the reaction is completed, the product is centrifuged to obtain a solid phase and a liquid phase; the solid phase is washed with water to neutrality, and dried in an oven at 60 ° C as the raw material R-7 for the subsequent reaction; 5 times the volume of hydrochloric acid aqueous solution with a pH of 2 is dripped into the liquid phase, stirring while dripping, and standing after dripping, and then centrifuged. The core was washed twice with a hydrochloric acid aqueous solution (pH = 2), and freeze-dried at -50 ° C for 24 hours to obtain lignin L-7; 0.1g of the obtained lignin L-7 was dissolved in 10mL of a low eutectic solvent, and 40mL of deionized water was uniformly dripped into it at a dripping rate of 0.2mL / s under ultrasonic and stirring conditions. After the titration, centrifugation was performed, and the solid phase was washed with deionized water until the supernatant was colorless, and the solid phase was freeze-dried at -50 ° C for 48 hours to obtain lignin nanospheres-7;

[0044] The raw material R-7 obtained above was used as a reaction raw material with pH = 5, with a solid-liquid ratio of 1:10 (1g raw material R-7: 10mL reaction solution), the reaction solution was a solution with pH = 5 (ethanol: water = 1:1, v / v, pH value adjusted to 5 with hydrochloric acid), reacted at 180°C for 1h, cooled after the reaction, and the product was separated by centrifugation to obtain a solid phase and a liquid phase; the solid phase was washed with water to neutrality, dried in an oven at 60°C, and used as the raw material R-5 for the subsequent reaction; 5 times the volume of a hydrochloric acid aqueous solution with pH = 2 was dripped into the liquid phase, and stirred while dripping Stir, let stand after dripping, centrifuge again, wash twice with hydrochloric acid aqueous solution (pH=2), freeze-dry at -50°C for 24h to obtain lignin L-5; dissolve the obtained 0.1g lignin L-5 in 10mL low eutectic solvent, drip 40mL of deionized water at a drip rate of 0.2mL / s under ultrasonic and stirring conditions, centrifuge after the titration, wash the solid phase with deionized water until the supernatant is colorless, freeze-dry the solid phase at -50°C for 72h to obtain lignin nanospheres-5;

[0045] The raw material R-5 obtained above was used as a reaction raw material with pH = 3, with a solid-liquid ratio of 1:10 (1 g raw material R-5: 10 mL reaction solution), the reaction solution was a solution with pH = 3 (ethanol: water = 1:1, v / v, pH value adjusted to 3 with hydrochloric acid), reacted at 180 ° C for 1 hour, cooled after the reaction, and the product was separated by centrifugation to obtain a solid phase and a liquid phase; the solid phase was washed with water to neutrality, dried in an oven at 60 ° C, and used as the raw material R-3 for the subsequent reaction; 5 times the volume of a hydrochloric acid aqueous solution with pH = 2 was dripped into the liquid phase, and stirred while dripping Stir, let it stand after dropping, centrifuge again, wash twice with hydrochloric acid aqueous solution (pH=2), and freeze-dry at -50°C for 24h to obtain lignin L-3; dissolve the obtained 0.1g lignin L-3 in 10mL low eutectic solvent, and drip 40mL of deionized water at a dripping rate of 0.2mL / s under ultrasonic and stirring conditions. After the titration is completed, centrifuge, wash the solid phase with deionized water until the supernatant is colorless, and freeze-dry the solid phase at -50°C for 72h to obtain lignin nanospheres-3.

[0046] Figure 1 This is the particle size distribution diagram of lignin nanospheres prepared from lignin L-7 in Example 1; Figure 2 This is the particle size distribution diagram of the lignin nanospheres prepared from lignin L-5 in Example 1.

[0047] analyze Figures 1-2 It can be found that as the pH value of the reaction system decreases, the particle size of the prepared lignin nanospheres gradually increases.

[0048] Example 2

[0049] An ethanol aqueous solution with a pH value of 5 (ethanol: water = 1:1, v / v, and the pH value is adjusted to 5 with hydrochloric acid) is used as a reaction liquid, and poplar wood powder is used as a raw material. The reaction is carried out at 120°C for 1 hour, and the solid-liquid ratio is 1:10 (1 g poplar wood powder: 10 mL reaction liquid). After the reaction is completed, the product is centrifuged to obtain a solid phase and a liquid phase; the solid phase is washed with water to neutrality, and dried in an oven at 60°C as a raw material R-120 for subsequent reactions; 5 times the volume of a hydrochloric acid aqueous solution with a pH value of 2 is dripped into the liquid phase, and stirring is performed while dripping. After the dripping is completed, the mixture is allowed to stand, and then the mixture is stirred for 2 hours. Centrifuge, wash twice with hydrochloric acid aqueous solution (pH=2), freeze-dry at -50°C for 48h to obtain lignin L-120; dissolve 0.1g of the obtained lignin L-120 in 10mL of a low eutectic solvent, drip 40mL of deionized water at a uniform rate of 0.2mL / s into it under ultrasonic and stirring conditions, centrifuge after the titration, wash the solid phase with deionized water until the supernatant is colorless, freeze-dry the solid phase at -50°C for 72h to obtain lignin nanospheres-120;

[0050] An ethanol aqueous solution with a pH value of 5 (ethanol: water = 1:1, v / v, and the pH value is adjusted to 5 with hydrochloric acid) is used as the reaction liquid, and the raw material R-120 obtained above is used as the raw material, and the reaction is carried out at 140°C for 1 hour, and the solid-liquid ratio is 1:10 (1g raw material R-120: 10mL reaction liquid). After the reaction, the product is cooled and centrifuged to obtain a solid phase and a liquid phase; the solid phase is washed with water until neutral, and dried in an oven at 60°C as the raw material R-140 for the subsequent reaction; 5 times the volume of a hydrochloric acid aqueous solution with a pH value of 2 is dripped into the liquid phase, and stirring is performed while dripping. After the dripping is completed, the mixture is allowed to stand, centrifuged again, washed twice with a hydrochloric acid aqueous solution (pH=2), and freeze-dried at -50°C for 24 hours to obtain lignin L-140; 0.1 g of the obtained lignin L-140 is dissolved in 10 mL of a low eutectic solvent, and 40 mL of deionized water is uniformly dripped into the mixture at a dripping rate of 0.2 mL / s under ultrasonic and stirring conditions. After the titration is completed, the mixture is centrifuged, and the solid phase is washed with deionized water until the supernatant is colorless, and the solid phase is freeze-dried at -50°C for 72 hours to obtain lignin nanospheres-140;

[0051] The above-obtained raw material R-140 is used as a raw material, and an ethanol aqueous solution with a pH of 5 (ethanol: water = 1:1, v / v, and the pH value is adjusted to 5 with hydrochloric acid) is used as a reaction liquid. The reaction is carried out at 160°C for 1 hour, and the solid-liquid ratio is 1:10 (1g raw material R-140: 10mL reaction liquid). After the reaction is completed, the product is cooled and centrifuged to obtain a solid phase and a liquid phase; the solid phase is washed with water until neutral, and dried in an oven at 60°C as the raw material R-160 for the subsequent reaction; 5 times the volume of a hydrochloric acid aqueous solution with a pH of 2 is dripped into the liquid phase, and stirring is performed while dripping. After the dripping is completed, let it stand, then centrifuge it, wash it twice with hydrochloric acid aqueous solution (pH=2), and freeze-dry it at -50°C for 24 hours to obtain lignin L-160; the obtained 0.1g lignin L-160 is dissolved in 10mL of low eutectic solvent, and 40mL of deionized water is dripped into it at a dripping rate of 0.2mL / s under ultrasonic and stirring conditions. After the titration is completed, centrifuge it, take the solid phase and wash it with deionized water until the supernatant is colorless, take the solid phase and freeze-dry it at -50°C for 72 hours to obtain lignin nanospheres-160.

[0052] Figure 3 This is the particle size distribution diagram of lignin nanospheres prepared from lignin L-120 in Example 2; Figure 4 This is a SEM image of lignin nanospheres prepared from lignin L-120 in Example 2; Figure 5 This is the particle size distribution diagram of the lignin nanospheres prepared from lignin L-140 in Example 2.

[0053] analyze Figures 3 to 5 It can be found that as the temperature of the reaction system increases, the particle size of the prepared lignin nanospheres gradually increases.

[0054] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0055] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for adjusting reaction conditions to extract lignin in a graded manner and prepare lignin nanoparticles of different particle sizes, characterized in that: The steps include: Step 1: mixing poplar wood powder and a solvent to react to obtain a solid phase and a liquid phase; Step 2: Using the solid phase as the raw material, repeat the reaction in step 1, and gradually reduce the pH value of the reaction system or gradually increase the temperature of the reaction system during the repetition process; The liquid phases obtained in step 1 and step 2 are respectively mixed with a hydrochloric acid solution, and washed and freeze-dried in sequence to obtain lignin; The low eutectic solvent is used as solvent and water is used as replacement solvent. The obtained lignin is treated by solvent replacement method to obtain lignin nanoparticles with different particle sizes.

2. The method according to claim 1, characterized in that The step of gradually reducing the pH value of the reaction system comprises: using the solid phase as a raw material, repeating step 1, and gradually reducing the pH value of the reaction system at a pH value of 7, 6, 5, 4, 3, 2 or 1, and the reaction temperature is 120-180°C.

3. The method according to claim 1, characterized in that The step of gradually increasing the temperature of the reaction system comprises: taking the solid phase as the raw material, repeating step 1, and gradually increasing the temperature of the reaction system at a temperature of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, and the pH value of the reaction is 1-7.

4. The method according to claim 2 or 3, characterized in that: The reaction time is 0.5 to 1 h.

5. The method according to claim 2 or 3, characterized in that: The solvent is an ethanol aqueous solution, in which the volume ratio of ethanol to water is 1:1-5; the solid-liquid ratio of the poplar wood powder to the solvent is 1g:5-10mL.

6. The method according to claim 2 or 3, characterized in that: The pH value of the hydrochloric acid solution is 2, and the volume ratio of the liquid phase to the hydrochloric acid solution is 1:5-10.

7. The method according to claim 2 or 3, characterized in that: The freeze drying temperature is -50°C, and the freeze drying time is 24 to 72 hours.

8. The method according to claim 2 or 3, characterized in that: The low eutectic solvent is prepared from lactic acid and choline chloride, and the mass ratio of the lactic acid to the choline chloride is 5 to 2:

1.

9. A method for regulating the particle size of lignin nanospheres, characterized in that: Poplar wood powder is used as raw material and ethanol aqueous solution is used as solvent. Lignin is extracted graded by adjusting the pH value of the reaction system or adjusting the temperature of the reaction system. Then the solvent replacement method is used to treat the obtained lignin to obtain lignin nanoparticles of different particle sizes.

10. The method according to claim 9, characterized in that Lignin nano-microspheres with gradually increasing particle sizes are obtained by gradually lowering the pH value of the reaction system; or, lignin nano-microspheres with gradually increasing particle sizes are obtained by gradually increasing the temperature of the reaction system.

Citation Information

Patent Citations

  • Method for preparing lignin and hemicellulose from wheat straws

    CN102603927A

  • Preparation method of lignin nanoparticles as well as product and application of same

    CN112080022A

  • Method for preparing size-controllable energy storage type lignin micro / nano spheres

    CN117024784A